Estratégia, poder e cooperação: um estudo de redes no setor de metalurgia de Cláudio MG - Rui Fernando Correia Ferreira (2015)
This study aims to identify the types of power relationships present in twelve metallurgic companies, part of the Associação das Indústrias Metalúrgicas de Cláudio ASIMEC, and to analyze how these relationships can influence on collaborative strategies formulation and implementation. This present case study collected information of managers and of their company networking in Cláudio, Minas Gerais. Data were collected through a methodological triangulation. In order to understand ASIMEC collaborative strategies it was used an analysis of content from qualitative data. Quantitative data were collected through Social Network Analysis and Simple Regression Analysis, as well as demographic and descriptive statistics data. The following sources of power were analyzed: (i) working networks, (ii) influence the external environment influences (iii) reputation, (iv) leadership, (v) learning, (vi) friendship (vii) hold resources management, (viii) strategic knowledge and (ix) cooperation in decision making. It was found that sources management and networking are important to gain competitive advantage and also for the development and implementation of collaborative strategies. The decision-making process is influenced by social structures interwoven. It is possible to understand the process of formulation and implementation of collaborative strategies by power relations between the actors of social networks. Work limitations are related to population size and data collection difficulties; the transversal time frame and the fact of contemplating only one case. This work contributes academically for deepening cooperation on issues such as, Collaborative Strategies and Power Relations, assisting managers in proactive and planned actions, regarding the formulation and implementation of strategies in an environment of organizational networking.